Down-hill creep of a granular material under expansion/contraction cycles - Jagla, Eduardo Alberto (2023)
We investigate the down-hill creep of a layer of granular material on a slope caused by an oscillatory variation of the size of the particles. The material is modeled as an athermal two dimensional polydisperse system of soft disks under the action of gravity. The slope angle is below the critical rest angle and therefore the system reaches an equilibrium configuration under static external conditions. However, under a protocol in which particles slowly change size in a quasistatic oscillatory way the system is observed to creep down in a synchronized way with the oscillation. We measure the creep advance per cycle as a function of the slope angle and the degree of change in particle size. In addition, we consider a situation in which the particle size oscillation amplitude decreases with depth, as it may be argued to occur in the case of a granular soil in an inclined terrain. In this case creep profiles that are maximum at the surface and smoothly vanish with depth are obtained, as it is observed to occur in the field.